Jogja Ora Didol : a Discourse of Resistance to Domination Through Music Norman Fairclough's Critical Discourse Analysis Study - Cahyaratri Hari Kinasih; Susanto Susanto; Warto Warto (Universitas Sebelas Maret, 2022)
The freedom of media since the death of the New Order has made its development so significant, especially in Indonesia. Artists have a platform to create creative ideas through media such as creating movies or music. The issue of power that is not in favor of the lower middle social class makes music present as a tool to respond to difficult situations and even become a tool of resistance to the government or those in power. This research is a qualitative study using Norman Fairclough's critical discourse analysis theory which has three dimensions in the text of the song Jogja Ora Didol by Jogja Hip-Hop Foundation. The musical background of Jogja Hip-hop Foundation and the language used in the song contain resistance. This study aims to see the extent to which the song Jogja Ora Didol influences and builds the power of resistance to the domination that exists in Yogyakarta. The song Jogja Ora Didol was created in conjunction with the many protests of empowered citizens against the massive construction of hotels in the Yogyakarta area. Resistance discourse is viewed from three levels, namely text, discourse-practice, and socio-cultural. This research aims to 1) Represent the text of the song Jogja Ora Didol, 2) The background of the creation of the song and 3) the influence of the song to create and build resistance. The results of this study show that the resistance of word units and metaphors form a unit of song text. In discourse practice, resistance is formed from the process of text production and consumption. Finally, in the sociocultural order, it is the macro factor that gives influence after the presence of Jogja Ora Didol song.